Online Learning in Border Isolated Areas on Temperature and Heat Materials - Amin Mustajab; Yulita Yulita (STKIP Singkawang, 2022)
Online learning in isolated areas is very difficult to implement, on the other hand direct learning cannot be carried out during this pandemic period. This study aims to see whether video-assisted learning (offline) is effective to be applied as an alternative in online learning. This quantitative study used a post-test only control-group design. The experimental class was treated with video-assisted teaching on the temperature and heat material. The control class was given learning treatment using the online learning method by giving assignments and online learning assisted by the whatsapp application. The population of this research is the seventh grade students of SMP Negeri 03 Entikong. The research sample amounted to 78 people were selected using a systematic sampling technique. The instrument in this study consisted of written test and video teaching on temperature and heat material. The written test given to students is in the form of an essay test with 4 questions related to heat material. The written test indicator consists of analyzing the temperature comparison of the thermometer; analyzing the effect of temperature on the long expansion of objects; using the specific heat data of material to determine the amount of heat required to raise the objects’ temperature; calculating the amount of heat to change the state of objects. The results of this study indicate that there is a difference between the average student physics’ learning outcomes in teaching video-assisted learning class and whatsapp-assisted online class.